Development of a low-cost flexible potentiometric detector and its integrated system for electrochemical sensing of electrolytes in human sweat - Chaojiang Li; Yuxuan Liu; Guodong Liu; Qifeng Tan; Xiaolong Dou; Yuting Xie; Xianchao Zhang (Sensors and Actuators Reports)
In the current era of wearable electrochemical sensors, there is a growing demand for a potentiometric detector that exhibits exceptional flexibility, comfortable wearability, and stability in electrolyte sensing. The present study designs and validates a low-cost (costs 17 dollars), small area (size of 4 × 5.8 cm2), highly flexible potentiometric detector, which is facilitated through the utilization of cost-effective components, flexible printed circuit boards, and Bluetooth low energy modules. Electrolyte electrochemical detection has been achieved by integrating wearable microfluidic electrochemical sensing devices and establishing wireless communication with smartphone applications. The efficacy of this designed flexible potentiometric detector is demonstrated in sodium and calcium ions detection, indicating comparable results to those obtained from commercial electrochemical workstations. By comparing the detection results with those obtained from ion chromatography, the flexible potentiometric detector is proved to be useful for a real-time, on-body quantitative analysis of various ion concentrations in human sweat.